INTERPERSONAL COMMUNICATION HUSBAND WIFE (Case Study: Why of affair between husband and wife) - Swastiningsih Swastiningsih (Avant Garde, 2016)
All creatures that exist in this world was created in pairs, it is characterized by the occurrence of a marriage that begins on the mutual attraction of the pair of the opposite sex. When there is a meeting, they then hold interaction where the interaction is inseparable from communication. Interpersonal communication that occurs is possible to implement the adaptation strategy to solve the problems. The theory used is the Information Manipulation Theory of Steven Mc Cornack (1992). This theory explains how people lie and how people be lied. The paradigm of constructivism and method of research is the first form of a case study. Conclusion: How do people lie, when facial expression does not match with the body language, likely that he lies. Infidelity in couples, not always originated from the conflict. There was also due to the hyper sex, habits, grudges, and there is a desire to try on different physical. The biggest factor causes infidelity is the present of their emotional conflicts that occur in the interpersonal relationship between husband and wife, where the conflict arisesJurnal Avant Garde Volume 4 Nomor 2 Desember 2016 90because of unmet emotional needs of her marriage partner. All that cheating will gain physical satisfaction, but morally, they are haunted by guilt prolonged. Suggestion. 1. If there are early symptoms of infidelity,